ApoB48 as an Efficient Regulator of Intestinal Lipid Transport - Lo, Chunmin C.; Coschigano, Karen T. (Frontiers in Physiology, 2020)
Fatty meals induce intestinal secretion of chylomicrons (CMs) containing apolipoprotein (Apo) B48. These CMs travel via the lymphatic system before entering the circulation. ApoB48 is produced after post-transcriptional RNA modification by Apobec-1 editing enzyme exclusively in the small intestine of humans and most other mammals. In contrast, in the liver where Apobec-1 editing enzyme is not expressed (except in rats and mice), the unedited transcript encodes a larger protein, ApoB100, which is used in the formation of very low-density lipoproteins (VLDL) to transport liver-synthesized fat to peripheral tissues. Apobec-1 knockout (KO) mice lack the ability to perform ApoB RNA editing and thus express ApoB100 in the intestine. These mice, maintained on either a chow diet or high fat diet, have body weight gain and food intake comparable to their wildtype (WT) counterparts on the respective diet; however, they secrete larger triglyceride (TG)-rich lipoprotein particles and at a slower rate than the WT mice. Using a lymph fistula model, we demonstrated that Apobec-1 KO mice also produced fewer CMs and exhibited reduced lymphatic transport of TG in response to duodenal infusion of TG at a moderate dose; in contrast, the Apobec-1 KO and WT mice had similar lymphatic transport of TG when they received a high dose of TG. Thus, the smaller, energy-saving ApoB48 appears to play a superior role in comparison with ApoB100 in the control of intestinal lipid transport in response to dietary lipid intake, at least at low to moderate lipid levels.